Pengaruh Kualitas Pelayanan (Offline) Dan Kualitas Digitalisasi Layanan (Online) Terhadap Kepuasan Peserta Pada Pt Taspen (Persero) - Asep Slamet Riyadi; Effed Darta Hadi; Muhammad Rusdi (Universitas Bengkulu, 2023)
The purpose of this study is to determine the effect of service quality (offline) on customer satisfaction, also to determine the effect of quality of service digitization (online) on customer satisfaction. The type of research used in this research is quantitative research. The data collection tool used a questionnaire distributed to 196 respondents studied, namely, member of PT Taspen (Persero) Palembang and Bengkulu Branch. The questionnaire was distributed online via google form. The validity test used in this study is convergent validity and discriminant validity with PLS 3.2.9 software. The reliability test uses the Cronbach's Alpha dan Composite Reliability with PLS 3.2.9 software. The analysis method used is inner model tested with path coefficients and R-Square analysis, also outer model tested with t tested. The results of this study indicate that (1) service quality has a significant and positive effect on customer satisfaction for member of PT Taspen (Persero). This means that the better quality of service that more satisfaction of participants who use the direct services provided by employees of PT Taspen (Persero). (2) the quality of service digitization has and positive effect on customer satisfaction for participants of PT Taspen (Persero) but not significant. This means that the better the quality of service digitization, the higher level of customer satisfaction of participants who use digital services of PT Taspen (Persero) but the impact is not significant.